2023
DOI: 10.3389/frph.2023.1084657
|View full text |Cite
|
Sign up to set email alerts
|

“PrEP protects us”: Behavioural, normative, and control beliefs influencing pre-exposure prophylaxis uptake among pregnant and breastfeeding women in Zambia

Abstract: BackgroundAlthough pre-exposure prophylaxis (PrEP) is recommended for pregnant and breastfeeding women at elevated HIV risk, uptake has been low in Zambia.MethodsIn in-depth interviews, we explored beliefs about PrEP among 24 HIV-negative pregnant and breastfeeding Zambian women. Thematic analysis was used to identify behavioural, normative and control beliefs likely to influence PrEP uptake.ResultsMost women viewed PrEP as a good method of protecting themselves and their babies from HIV infection. Partners we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The factors associated with PrEP use identified by this study included having a known HIV-positive male partner, a male partner with unknown HIV status, positive attitudes towards PrEP, high self-efficacy, having tested for an STI in the last 6 months, and having taken PEP in the last 6 months. This finding aligns with previous studies conducted in Zambia and Kenya among PPW where factors associated with PrEP use were: being a sero-different couple, having a partner of unknown HIV status, having a positive attitude towards PrEP ( 47 ), and a reactive syphilis test result ( 7 ). Some studies identified other pertinent factors for PrEP use such as: engaging in sex without a condom in the past six months, having experienced intimate partner violence ( 7 , 29 ), the desire to safely conceive a child ( 23 ), being a drug injector, being homeless ( 48 ) and rape ( 29 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The factors associated with PrEP use identified by this study included having a known HIV-positive male partner, a male partner with unknown HIV status, positive attitudes towards PrEP, high self-efficacy, having tested for an STI in the last 6 months, and having taken PEP in the last 6 months. This finding aligns with previous studies conducted in Zambia and Kenya among PPW where factors associated with PrEP use were: being a sero-different couple, having a partner of unknown HIV status, having a positive attitude towards PrEP ( 47 ), and a reactive syphilis test result ( 7 ). Some studies identified other pertinent factors for PrEP use such as: engaging in sex without a condom in the past six months, having experienced intimate partner violence ( 7 , 29 ), the desire to safely conceive a child ( 23 ), being a drug injector, being homeless ( 48 ) and rape ( 29 ).…”
Section: Discussionsupporting
confidence: 90%
“…Our study found other reasons for PrEP discontinuation including; unavailability of PrEP and being stopped by partner or husband. Consistent findings from regional studies reported PrEP stock-outs and needing partner or husband approval to take PrEP as barriers to PrEP uptake, adherence and retention ( 23 , 39 , 47 ). The lack of autonomy among women to make decisions concerning their health may present a barrier to PrEP uptake.…”
Section: Discussionmentioning
confidence: 58%
“…By contrast, other studies with MSM have described uncertainty over a partner’s sexual relationships with others as facilitating their PrEP use [ 30 , 34 ]. Relationship-related barriers served as among the reasons given for recommendations that PrEP be offered as an injectable, so that PrEP could be used with more discretion, a finding noted in other qualitative studies on PrEP preferences among different PP groups in Zambia [ 40 , 48 , 49 ]. That said, some studies have described the benefits of PrEP-use disclosure to intimate partners for adherence and stigma-management [ 50 ], though this comes with fear of violence [ 51 ].…”
Section: Discussionmentioning
confidence: 92%
“…Their knowledge and positive attitudes toward PrEP can influence its acceptance and uptake among pregnant women [ 53 , 54 ]. Furthermore, integration of HIV services into maternal health settings has been shown to improve the uptake and retention of services related to prevention of mother-to-child transmission (PMTCT) [ 55 , 56 ]. This integration can lead to increased awareness and acceptance of HIV prevention strategies including PrEP.…”
Section: Discussionmentioning
confidence: 99%